2020
DOI: 10.1111/jace.17525
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis and antibacterial properties of thermally sintered apatites with varied processing conditions

Abstract: Biological waste holds a major portion of the municipal waste stream, particularly in rural areas of developing countries. According to the Food and Agriculture Organization of the United Nations (FAO), every year there are 1.3 billion tons of food waste produced and around one-third of all food produced for human consumption are being wasted. 1 Amongst the other sources, the livestock industry (fish and poultry industry) has a vital contribution. Some biological

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
(140 reference statements)
1
8
0
Order By: Relevance
“…Out of 71 relevant article titles collected from SCOPUS, PubMed, and Google Scholar, only 36 were included after screening the title, abstract, and content for in vitro degradation and cytotoxicity testing for the biocompatibility of eggshell-based hydroxyapatite. The articles came from several countries, such as India [ 11 , 14 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], Bangladesh [ 41 , 42 ], China [ 43 ], Korea [ 25 , 44 , 45 ], Turkey [ 46 , 47 , 48 ], Thailand [ 49 , 50 ], Brazil [ 26 ], Italy [ 51 ], USA [ 52 ], Romania [ 2 ], Vietnam [ 53 , 54 ], Colombia [ 55 ], and Egypt [ 56 ]. The study selection of the articles included in the systematic review is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of 71 relevant article titles collected from SCOPUS, PubMed, and Google Scholar, only 36 were included after screening the title, abstract, and content for in vitro degradation and cytotoxicity testing for the biocompatibility of eggshell-based hydroxyapatite. The articles came from several countries, such as India [ 11 , 14 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], Bangladesh [ 41 , 42 ], China [ 43 ], Korea [ 25 , 44 , 45 ], Turkey [ 46 , 47 , 48 ], Thailand [ 49 , 50 ], Brazil [ 26 ], Italy [ 51 ], USA [ 52 ], Romania [ 2 ], Vietnam [ 53 , 54 ], Colombia [ 55 ], and Egypt [ 56 ]. The study selection of the articles included in the systematic review is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…It means that there should not be a decrease of viable cells of more than 30% [ 26 ]. In the analysis of the studies we conducted, the cultured cells came from humans and animals, including mice [ 27 , 35 , 40 ], rats [ 25 , 33 , 36 ], and monkeys [ 41 , 42 ]. As shown in Table 3 and Table 4 , with the varieties of cell cultures used, all studies obtained viable cell results of more than 70% with a variety of materials, either pure eggshell-based hydroxyapatite or composites of eggshell-based hydroxyapatite and other materials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations